2012
DOI: 10.1021/ml3001352
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible 4-Aminopiperidine Transglutaminase 2 Inhibitors for Huntington's Disease

Abstract: A new series of potent TG2 inhibitors are reported that employ a 4-aminopiperidine core bearing an acrylamide warhead. We establish the structure−activity relationship of this new series and report on the transglutaminase selectivity and in vitro ADME properties of selected compounds. We demonstrate that the compounds do not conjugate glutathione in an in vitro setting and have superior plasma stability over our previous series. KEYWORDS: plasma stability, computer-aided drug design, SAR, acrylamides, Celiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…More potent and selective irreversible TG2 inhibitors carrying an acrylamide moiety have recently been reported ( 1 – 3 in Fig. 3 ) (Prime et al 2012a , b ; Wityak et al 2012 ). Conveniently, carbon-11 radiosynthesis of acryl amides has been reported using various strategies resulting in the carbon-11 atom at the acrylamide carbonyl position, rendering this class of Michael acceptor inhibitors amenable to radiolabelling (Eriksson et al 2007 ).…”
Section: Irreversible Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…More potent and selective irreversible TG2 inhibitors carrying an acrylamide moiety have recently been reported ( 1 – 3 in Fig. 3 ) (Prime et al 2012a , b ; Wityak et al 2012 ). Conveniently, carbon-11 radiosynthesis of acryl amides has been reported using various strategies resulting in the carbon-11 atom at the acrylamide carbonyl position, rendering this class of Michael acceptor inhibitors amenable to radiolabelling (Eriksson et al 2007 ).…”
Section: Irreversible Inhibitorsmentioning
confidence: 99%
“…Other potent acrylamide inhibitors based on an aminopiperidine core have been reported. Apart from [ 11 C]CO aminocarbonylation, the strongest inhibitor within this class, compound 9q , potentially allows for radiolabelling at the methoxy position by straightforward [ 11 C]MeI methylation of the corresponding O-desmethyl precursor (Prime et al 2012b ). Recently, Badarau et al also reported on the development of potent TG2 inhibitors carrying the acrylamide moiety (Badarau et al 2015 ).…”
Section: Irreversible Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other irreversible inhibitors that are not based on peptides have also been designed. 270,271 Of the other binding sites on TG2, only the GTP binding site has been targeted by an inhibitor, Tyrphostin 47, an epidermal growth factor receptor (EGFR) kinase inhibitor that binds to TG2 competitively with GTP. 272 Some kinaserelated inhibitors of TG2 have been found, but are competitive inhibitors of enzyme activity, 272 not (as far as is known) allosteric inhibitors acting through the GTP site.…”
Section: Tg2 Inhibitorsmentioning
confidence: 99%
“…Acrylamide moieties have been used to functionalize lead compounds by several researchers to develop irreversible inhibitors for some classes of proteins [2,3,4,5]. This acrylamide “warhead” can form a covalent interaction via alkylation with conserved Cys residues in the active sites of these proteins.…”
Section: Introductionmentioning
confidence: 99%